1981
DOI: 10.1016/s0003-2670(01)93571-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a 9-mm inductively-coupled argon plasma source for atomic emission spectrometry

Abstract: torches. g-mm TheThe 13 vided. Figure Figure 1 1 Fig. 1 sho"n in in Fig. 2, 2,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Therefore, the relationship between the plasma gas flow rate and the RF power is plotted. The consumption of the plasma gas is slightly reduced upon air-cooling, but compared with the conventional Ar-ICP torch and low argon gas consumption torches, 2,3,8 there is an expansion of suitable conditions needed to generate stable Ar-ICP. With the new torch, it is possible to generate stable doughnut-shaped Ar-ICP with lower RF power and a lower plasma gas condition compared with the conventional ICP torch.…”
Section: Experimental Conditions For Stable Plasma Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the relationship between the plasma gas flow rate and the RF power is plotted. The consumption of the plasma gas is slightly reduced upon air-cooling, but compared with the conventional Ar-ICP torch and low argon gas consumption torches, 2,3,8 there is an expansion of suitable conditions needed to generate stable Ar-ICP. With the new torch, it is possible to generate stable doughnut-shaped Ar-ICP with lower RF power and a lower plasma gas condition compared with the conventional ICP torch.…”
Section: Experimental Conditions For Stable Plasma Generationmentioning
confidence: 99%
“…To reduce consumption of the plasma gas, low-flow-rate Ar-ICP torches have been studied. 1 These include a mini-ICP torch, 2 a small-diameter ICP torch, 3,4 a water-cooled torch for low-flow ICP, 5,6 an externally air-cooled low-flow torch, 7 and a high-efficiency torch (HE torch). 8 Other problems are polyatomic ions interference, and insufficiency of the excitation/ionization ability of Ar-ICP.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly attractive group of ICP-OES sources for potential use in ICP-MS are those supported by alternative plasma torches [85][86][87][88][89][90][91][92]. Especially smaller (13-mm [85-90] and 9-mm [85,86,91]) torches have been found to offer compara-ble analytical utility but with reduced power and argon requirements.…”
Section: Alternative Plasma Sourcesmentioning
confidence: 99%
“…Especially smaller (13-mm [85-90] and 9-mm [85,86,91]) torches have been found to offer compara-ble analytical utility but with reduced power and argon requirements. Further improvements in performance have been observed with these smaller plasma torches when the rf operating frequency is increased [85].…”
Section: Alternative Plasma Sourcesmentioning
confidence: 99%
“…This is also a crucial problem in underdeveloped countries because Ar gas is either unavailable or too expensive. In order to reduce the Ar plasma gas flow rate for the sake of decreasing running cost as well as avoiding problems, low gas flow torches such as a high efficiency torch, 4,5 a reduced size (mini) torch, [6][7][8][9] a water cooled torch, [10][11][12][13] an air cooled torch, [14][15][16] and so on, were developed and those performances were examined especially for mostly radial viewing OES. It was reported that the high efficiency torches and the reduced size ones could sustain ICPs under the Ar plasma gas flow rate from 4 to 12 L min -1 with radio frequency (RF) forward power from 0.5 to 1.2 kW.…”
Section: Introductionmentioning
confidence: 99%